Metodología para el control de gestión en la Asociación de mujeres comunitarias del cantón Tosagua - Cotera Mantilla, Stefany Yicel (2021)
The economy is subject to the commercial sector and in turn allows society to develop, however, there are many companies or associations that lack good management, which is why the objective of this research is focused on determining a methodology for the control of management in the AMUCOMT association of the Canton Tosagua. Being this research of bibliographic and field type, techniques of surveys, interviews and observation were applied. In addition, tools such as interview guides, questionnaires and observation guides were used, which allowed us to adequately collect strategic information in order to apply the management methodology. Likewise, the SPSS technological tool was used for data analysis. In the applied diagnosis, it was observed that there is a lack of control management since shortcomings were identified in terms of an organizational structure and socialization of relevant data of the association, in addition to this, the respondents stated that the effectiveness of control in the processes administrative is regular. The respective comprehensive scorecard was prepared where management indicators were identified that were related to four perspectives that were later evaluated using the traffic light technique in which it was determined that the financial part and the learning part are in the color red, therefore, the association is forced to improve these aspects as soon as possible. Finally, the proposed methodology was applied making use of the strategic plan of the association, improving its management.